Reavaliação de doses agudas de benzodiazepínicos como modelo de amnésia anterógrada - Segura, Isis Angélica [UNIFESP] (2019)
Acute benzodiazepines (BZ) administration is regarded as a pharmacological model of unspecific organic anterograde amnesia. Objectives: To establish which type of amnesia BZs best model. To this end we determined the acute effects of the BZ compound diazepam on cognitive processes that have not been investigated in the BZ literature and that distinguish different types amnesia: susceptibility to retroactive interference and accelerated forgetting. We also investigated the effects on working memory capacity (WMC), which is important for episodic memory encoding and retrieval. Methods: Thirty young, healthy undergraduates participated in this doubleblind, parallel-group design experiment in which participants were randomly allocated to one of two acute oral treatments: diazepam (15 mg) or placebo. Baseline performances on two WMC tasks and immediate free-recall of stories were initially assessed. One of these stories was immediately followed by 10 min of Retroactive Interference (RI), that is, spotting differences in pictures and another by Minimum RI (MinRI), or quiet rest in a darkened room. The tasks were repeated after treatment, followed by a surprise delayed free-recall of all 4 presented stories, which allowed their reconsolidation under both treatments. At the end of the post-treatment session, two other stories were presented following the RI and MinRI protocol and subjected only to immediate free-recall (no reconsolidation post-treatment). In a treatment-free session after 7 days, a surprise delayed recall of all stories was carried out to assess memory decay. Results: Diazepam elicited profound anterograde amnesia for story content consolidated and reconsolidated under the drug treatment, slightly impaired immediate free-recall but did not affect retrieval of stories presented pre-treatment, WMC, nor increased susceptibility to RI or accelerated forgetting of prose consolidated and reconsolidated under the effect of the BZ. Conclusion: The cognitive profile induced by acute administration of diazepam is similar to that of patients with organic anterograde amnesia resulting from insults to hippocampal structures involved in consolidation/reconsolidation of episodic memories.